2000
DOI: 10.1042/cs19990205
|View full text |Cite
|
Sign up to set email alerts
|

Muscle function during fatigue in myoadenylate deaminase-deficient Dutch subjects

Abstract: Myoadenylate deaminase (MAD) is an enzyme active in skeletal muscle, probably during exercise of moderate intensity but certainly during vigorous exercise, when the deamination of AMP leads to increased levels of IMP and ammonia. There is controversy about the clinical significance of MAD deficiency. The main objective of the present study was to investigate the extent to which genetically confirmed MAD deficiency affects muscle function under conditions of maximal short-term electrically induced activation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…If necessary, the timing of the superimposed octet, which was set at an individually adjusted time (usually 1.5-3 s after torque onset) before each attempt, was adjusted. From the attempt with the highest value of VA, the MTC of the knee extensors was calculated using the equation MTC ϭ (maximal voluntary torque) ⅐ VA Ϫ1 ⅐ (100%) Ϫ1 (12). MTC is an estimate of the maximal isometric torque under conditions of maximal muscle activation.…”
Section: Subjectsmentioning
confidence: 99%
“…If necessary, the timing of the superimposed octet, which was set at an individually adjusted time (usually 1.5-3 s after torque onset) before each attempt, was adjusted. From the attempt with the highest value of VA, the MTC of the knee extensors was calculated using the equation MTC ϭ (maximal voluntary torque) ⅐ VA Ϫ1 ⅐ (100%) Ϫ1 (12). MTC is an estimate of the maximal isometric torque under conditions of maximal muscle activation.…”
Section: Subjectsmentioning
confidence: 99%
“…Thus, whether AMPD deficiency alters exercise performance is still unresolved. Previous studies have examined this issue with conflicting results: some reporting diminished performance (5,26,28), and others normal performance (6,25,29,33) in AMPD-deficient subjects. There are several factors that may have contributed to variable outcomes across studies, such as a relatively small sample size, the type of exercise employed, and the presence of other neuromuscular complications in deficient subjects.…”
mentioning
confidence: 99%
“…Therefore, Ruiter et al concluded that changes in contractile properties of the human adductor pollicis muscle in response to 60 electrically induced shortening contractions were similar for AMPD deficient individuals and the control group. In other words, the absence of AMPD appeared to have no functional consequences despite the decrease in PP [16].…”
Section: Introductionmentioning
confidence: 91%
“…A number of studies have examined different performance parameters or markers of muscle metabolism in relation to the expression of AMPD1 with varied findings [14][15][16][17][18]. Fischer et al examined metabolic differences across AMPD1 genotypes and the influence on muscle power [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation